START Triage Sebagai Istrumen Penanganan Korban dalam Setting Bencana - Bayu Budi Laksono (Nursing Information Journal, 2024)
Unexpected incidents that result in significant loss or destruction are called disasters. In general, this event is closely associated with natural phenomena. Ultimately, though, this is frequently linked to incidents brought about by human intervention that entail drastic lifestyle modifications and significant harm. Since it is vital to allocate comparatively few resources to specific, urgent medical needs, triage is a crucial component of contemporary medical treatment. When a patient's medical demands and the resources that are available are not met in a timely or convenient manner, this task becomes critical. The foundation of Simple Triage and Rapid Treatment (START) is a quick evaluation of mental status, breathing, and perfusion (RPM). This work was written using a literature study methodology. Reference books (textbooks), scientific journals, and other pertinent sources provide the literature that is used. According to calibration and discrimination data, RPM (STARt triage) is a more reliable indicator of the blunt trauma survival rate than the Trauma Severity Score and the Revised Trauma Score. SALT triage is inferior to START (SMART) triage. On the other hand, employing START triage has been shown to increase time efficiency. It has been scientifically demonstrated that using START triage can result in suitable assessments for disaster management. Through the development of the Mass Casualty Triage Pack (SMART Triage Pack), STRAT triage has been used to enhance its efficacy.